Alkylguanidinium based ionic liquids in a screening study for the removal of anionic pollutants from aqueous solution. Issue 45 (19th April 2016) - Bouchal, Roza; Prelot, Bénédicte; Hesemann, Peter
Abstract : Monoalkylguanidinium bis-trifluoromethane sulfonimides are highly efficient adsorbents for the sequestration of organic anions from aqueous solutions and display strongly enhanced adsorption properties compared to conventional imidazolium ILs. Abstract : Monoalkylguanidinium bis-trifluoromethane sulfonimides are water immiscible functional ionic liquids which appear as highly efficient phases for the sequestration of anionic pollutants from aqueous solutions. The new compounds show significantly enhanced extraction efficiency compared to conventional imidazolium based ionic liquids.